PENINGKATAN HYGIENE PERSONAL PADA ANAK JALANAN DENGAN MEDIA KOMIK DI UPTD KAMPUNG ANAK NEGERI LIPONSOS KECAMATAN MEDOAN AYU RUNGKUT SURABAYA - Reliani **, Anis Rosyiatul Husna* Reliani ** (Universitas Muhammadiyah Jember, 2016)
Street children are children aged 5-18 years, both men and women who spend the majority of time on the road. The amount of activity on the streets cause they do not pay attention to personal hygiene. This leads them vulnerable to many disease, such as scabies, roundworm, tracoma, conjunctivitis, and thypoid. This study aim to identification enhancement of personal hygiene in street children with comics media at UPTD Kampung Anak Negeri Liponsos Kecamatan Medoan Ayu Rungkut Surabaya. The research used pre-post experimental design. Simple random sampling had been used to collect 22 street children at UPTD Kampung Anak Negeri Liponsos Kecamatan Medoan Ayu Rungkut Surabaya. The instrument are comic and questionnaire. The data analized with SPSS Wilcoxon statistic test. The result before intervention showed more than half (54,4%) personal hygiene behavior in moderate category, and 77,3 % after intervention in good category. The result of statistic test showed p=0.000 < alpha=0.05, this means there was a significant different pre and post intervention comic media. We hope comic media education can be use for school and adolescent children acording to their age.Keywords : Street children, personal hygiene, comic